TRANSPLANTATION OF NEURAL PROGENITOR CELLS IN CHRONIC SPINAL CORD INJURY - Jin, Y. (Neuroscience, 2016)
Previous studies demonstrated that neural progenitor cells (NPCs) transplanted into a subacute contusion injury improve motor, sensory, and bladder function. In this study we tested whether transplanted NPCs can also improve functional recovery after chronic spinal cord injury (SCI) alone or in combination with the reduction of glial scar and neurotrophic support. Adult rats received a T10 moderate contusion. Thirteen weeks after the injury they were divided into four groups and received either: 1. Medium (control), 2. NPC transplants, 3. NPC + lentivirus vector expressing chondroitinase, or 4. NPC + lentivirus vectors expressing chondroitinase and neurotrophic factors. During the 8 weeks post-transplantation the animals were tested for functional recovery and eventually analyzed by anatomical and immunohistochemical assays. The behavioral tests for motor and sensory function were performed before and after injury, and weekly after transplantation, with some animals also tested for bladder function at the end of the experiment. Transplant survival in the chronic injury model was variable and showed NPCs at the injury site in 60% of the animals in all transplantation groups. The NPC transplants comprised less than 40% of the injury site, without significant anatomical or histological differences among the groups. All groups also showed similar patterns of functional deficits and recovery in the 12 weeks after injury and in the 8 weeks after transplantation using the Basso, Beattie, and Bresnahan rating score, the grid test, and the Von Frey test for mechanical allodynia. A notable exception was group 4 (NPC together with chondroitinase and neurotrophins), which showed a significant improvement in bladder function. This study underscores the therapeutic challenges facing transplantation strategies in a chronic SCI in which even the inclusion of treatments designed to reduce scarring and increase neurotrophic support produce only modest functional improvements. Further studies will have to identify the combination of acute and chronic interventions that will augment the survival and efficacy of neural cell transplants.